Sensitivity of microscopy compared to molecular diagnosis of p. Falciparum: implications on malaria treatment in epidemic areas in kenya - Wangai, L.N.; Karau, M.G.; Njiruh, Nthakanio P.; Sabah, O.; Kimani, F.T.; Magoma, G.; Kiambo, N. (My University, 2011)
Detection of Plasmodium species by microscopy has been the gold standard for diagnosis of malaria for more than a century. Despite the fact that there is a significant decline in the number of positive cases reported from microscopy, antimalarial drugs prescriptions are on continuous increase as patients present with symptoms of malaria. This makes it difficult to establish accuracy, sensitivity and specificity of light microscopy in diagnosis of malaria in epidemic areas. This study was designed to compare microscopy with polymerase chain reaction as diagnostic methods for malaria in three epidemic areas in Kenya. A total of 356 patients presenting with malaria symptoms were diagnosed by microscopy and dried blood filter paper spots were collected from patient in Kisii, West Pokot and Narok districts. Plasmodium falciparum DNA was extracted from the dried blood filter samples. Primers specific for the Plasmodium Species were designed and used in a two step amplification of the Pfmdr gene. The PCR products were analyzed in ethidium bromide stained 1.5% agarose gel. It was found that 72 out of 350 specimens diagnosed as negative were positive for P. falciparum by nested PCR, while 6 which were microscopy positive were confirmed so by nested PCR. This study demonstrates that there is a high level of misdiagnosis which may either lead to denial for deserved treatment or undeserved treatment. Nested PCR detection of malaria parasites is a very useful complement to microscopy although it is expensive and takes long time. Additionally, smear negative patients suspected to have malaria should be subjected to PCR diagnosis to improve rational drug use. The economic burden of misdiagnosis and mistreatment of malaria outweighs that of PCR diagnosis, hence this diagnostic mode could be tenable in the long run even in rural areas
Keywords: Plasmodium falciparum; diagnosis; epidemics; microscopy; polymerase chain reaction